أثر أ رس المال الفكري على الإفصاح المحاسبي بالقوائم المالیة للشركات المساهمة العامة الصناعیة الأردنیة –د ا رسة تطبیقیة - sauoud elkhadi, lama fares (Finance and Business Economies Review, 2018)
This study aimed to identifying the intellectual capital and its impact on accounting disclosure in the financial statements of the Jordanian industrial public shareholding companies through studying the dimensions of intellectual capital efficiency (human capital efficiency, structural capital efficiency, and capital adequacy efficiency) on the level of accounting disclosure of Jordanian Industrial public shareholder Companies. The sample of the study consisted of 39 Jordanian industrial public shareholding companies listed on the Amman Stock Exchange for the year 2016. The disclosure indicators were obtained through financial reports for the year ended at 31/12/2016. In order to analyze the data obtained from financial reports simple and multiple linear regressions analysis was performed to test the hypotheses. The study recommended the adoption of a clear strategy related to the development of intellectual capital and its components in industrial companies and executes it because of its strategic role in achieving the objectives of companies. Industrial companies need to increase their expenditures allocated to the scientific research and development to improve the company's production and operational operations, and increase administrative efficiency and productivity of workers. Industrial companies need to pay more attention to increase the level of investment in human capital, and to the process of developing competencies, skills وabilities, and stimulating creativity and innovation among employees, through providing incentives in various forms.